Low Power-High Gain Bulk-Driven 3 Stages CMOS Miller OTA in 130nm Technology - Engin Afacan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2020)
The requirement of low-power analog circuits has been raised in recent years due to the strict limitation of power consumption in modern applications. Therefore, the trend in analog circuit design has been changed such that they are able to meet the required specifications with lower power dissipation. Design of low power operational transconductance amplifiers, which are the main building blocks in many analog applications, has been more pronounced to keep the power dissipation below certain levels. In this concern, this study presents a low power, high-performing bulk-driven 3 stages CMOS OTA in a 130 nm standard CMOS technology. The proposed circuit leverages the bulk-driven architecture at the input stage; thus it can operate under sub 1-V. The design process of the proposed OTA is explained in detail and the results are validated via post-layout simulations. The proposed OTA is powered by ±0.45 V symmetric voltage sources, where the power consumption is around 27 μW. The area overhead is only 0.0017μm2. The open-loop gain, unity gain frequency, and the phase margin are 73.24 dB, 5.167MHz, and 78o, respectively. To demonstrate the performance of the proposed circuit, a comparison is made with other circuits published in the last five years considering the well-known figures of merit (FOMs). Comparison results indicate that the proposed solution outperforms the other circuits for small-signal operation while it is the runner-up for large-signal operation.